Investigating Factors Influencing the Choice of Nepalese Students’ Decision to Study Abroad - Mahara, Simran (Nepalese Journal of Economics, 2025)
This study examines the factors influencing the choice of Nepalese students’ decision to study abroad. Decision to study abroad is the dependent variable. The selected independent variables are motivational factors, socioeconomic factors, educational factors, cultural and social factors, personal factors, government policies, and programs. The primary source of data is used to assess the opinions of respondents regarding motivational factors, socioeconomic factors, educational factors, cultural and social factors, personal factors, government policies, and programs. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of decision to study abroad on students’ in Nepal. The study shows that motivational factors have positive impact on decision to study abroad. It indicates that better motivational factors such as interests and passions, reputation of foreign universities lead to increase in decision to study abroad. Similarly, socio-economic factors have positive impact on decision to study abroad. It indicates that socio-economic factor like family’s financial stability leads to increase in decision to study abroad. Likewise, educational factors have positive impact on decision to study abroad. It indicates that educational factors such as reputation and ranking of foreign universities influenced students’ decision to study abroad. Further, cultural and social factors have positive impact on decision to study abroad. It indicates that cultural and social factors like family or friends who studied abroad leads to increase in decision to study abroad. In addition, personal factors have positive impact on decision to study abroad. It indicates that personal factors such as health and wellness and personal growth lead to increase in decision to study abroad. Moreover, government policies and programs also have positive impact on decision to study abroad. It indicates that flexible government policies and programs lead to increase in decision to study abroad.